GOTONG ROYONG PADA MASYARAKAT HINDU BALI SEBAGAI PEDOMAN MENYONGSONG ERA SOCIETY 5.0 - Darma Permana, I Dewa Gede (Widya Katambung, 2024)
Abstract The arrival of the Society 5.0 era has accelerated the development of technology and information. On the one hand, technological developments make all activities run more effectively and efficiently. But on the other hand, technological developments can also degrade the noble values that exist in society. For this reason, it is necessary to replant the noble values of life, such as the concept of Ekasila 'Gotong Royong' in Hindu society in Bali. Based on these problems, this research tries to examine more holistically the concept of gotong royong and its implementation in Balinese Hindu society. Through this topic, 3 discussions were formulated, including the essence of Ecasila, several concepts of gotong royong in Balinese Hindu society, and the implications of gotong royong as a guideline in welcoming the era of Society 5.0. By using a qualitative research method with a descriptive approach, as well as data collection using literature studies and Miles and Huberman data analysis, this study found that the concept of Ekasila 'Gotong Royong' in Balinese Hindu society can be a noble and noble guideline in welcoming the era of Society 5.0. Keywords: Ekasila, Gotong Royong, Society 5.0